'I was cracking more than everyone else': young adults' daily life experiences of hypermobility and jaw disorders. (11th January 2020) - Ilgunas, Aurelia; Wänman, Anders; Strömbäck, Maria
Abstract : Most studies on general joint hypermobility (GJH) and temporomandibular disorders (TMD) are quantitative and have concluded that joint hypermobility is a risk factor for development of TMD. The present qualitative study aimed to explore young adults' daily life experiences of GJH, specifically these relating to jaw function, and their experiences of medical and dental care providers. Semi‐structured interviews were conducted with nine young adults (18–22 yr of age) and data were analysed using qualitative content analysis. The overarching thematic category that emerged was 'Hypermobility in daily life', which was broken into six subthemes and three themes: 'emotional perception', 'dealing with symptoms', and 'outside influences'. Participants' narratives centred on experiences of complex symptoms, awkward jaw function and joint noises, feeling different, and a lack of support from general medical and dental care providers. The findings show that young adults with joint hypermobility need early support from medical and dental care providers for managing their symptoms and conditions related to GJH. Future studies are warranted to develop guidelines for professionals in medical and dental care to detect and prevent forthcoming problems and to offer relevant support to hypermobile youths.